Student Mathematical Communication in Online Discussion in Introduction to Geometry Course using Edmodo - Qohar, Abd; Fazira, Shima Kunaza (LPPM Undiksha, 2022)
Mathematical communication is an important part in learning mathematics. Mathematical communication is a way for students to express mathematical ideas either orally, in writing, pictures, diagrams, using objects, presenting in algebraic form, or using mathematical symbols. Through mathematical communication, students can convey ideas and clarify understanding and knowledge during the mathematics learning process. Mathematical communication skills are important because in learning mathematics, the use of notation, symbols, formulas and terms is a determining factor in problem solving. Due to the pandemic, learning activities are carried out online through Edmodo. This may bring changes to students' mathematical communication when doing a discussion. For this reason, this research aims to describe students' mathematical communication during discussion session in the Introduction to Geometry course through Edmodo. This research is a qualitative descriptive research. The subjects of this research were 35 students of first semester mathematics education who were taking the Introduction to Geometry course. The results showed that in doing a discussion, the students used written, visual, and symbolic mathematical communication. In expressing their opinion, students can also use more than one type of mathematical communication. In addition, the opinions expressed in the discussion were at various cognitive levels.